Nonstranger Victimization and Inmate Maladjustment: Is the Relationship Gendered?. (August 2016) - Cain, Calli M.; Steiner, Benjamin; Wright, Emily M.; Meade, Benjamin
Scholars have hypothesized that victimization elicits distinctive effects on women's pathways to prison and subsequent prison maladjustment, but few researchers have investigated gender differences in this relationship. Using nationally representative samples of men and women housed in state prisons, we examine gender differences in the effects of experiencing different types of nonstranger victimization prior to prison on inmate maladjustment. Results indicate that pre-prison nonstranger victimization affects men's and women's maladjustment similarly, with some gender differences—specifically, the effect of being physically assaulted by a nonstranger as an adult on violent misconduct was stronger among men, as was the effect of child abuse on men's depressive symptoms. Our findings suggest the effects of experiencing nonstranger victimization prior to incarceration on prison maladjustment may be gender-neutral more so than gender-specific. Based on our findings, nonstranger victimization should be deemed important in theories of men's maladjustment as well as in theories of women's maladjustment.